Peranan Sumber Daya Pendidikan sebagai Faktor Penentu dalam Manajemen Sistem Pendidikan - APRIYANTI WIDIANSYAH (Universitas Bina Sarana Informatika, 2018)
Education is a very important factor in human life, so the process of developing human resources must be carried out by increasing knowledge, skills and attitudes and values so that they can adapt to their environment. Qualitative Research Approach and Type of Descriptive Research, with a view to obtaining an overview of the dimensions of correlativeness of the synergy of the Role of Educational Resources as the Determinants in the Management of the Education System in this study. With the hope of building a whole substantive thought (not dichotomous and partial). After finding qualitative data, to be analyzed based on observations or findings that exist in the field. The results of this study indicate that the problem of human resources is very dominant in the Process of education / learning, this also means that managing human resources is a very important field in carrying out the learning process in schools.